(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper focuses on the effect of distance variation between the triangles in a bow tie antenna which basically consists of two triangles shaped metals facing towards each other separated by a distance and arranged in a configuration of a bow tie structure. It is generally feed through a coaxial cable at the centre of the separation distance to achieve an impedance matching. It is the preferred structure because of its simplicity and capability of transmitting and receiving broad range of frequencies and hence known as broadband bow tie antenna (BBTA).